Immunomodulatory effects of canine mesenchymal stem cells in an experimental atopic dermatitis model - Kang, Seok-Jin; Gu, Na-Yeon; Byeon, Jeong Su; Hyun, Bang-Hun; Lee, Jienny; Yang, Dong-Kun (Frontiers in Veterinary Science, 2023)
Background: Mesenchymal stem cells (MSCs) have the potential to differentiate into multi-lineage cells, suggesting their future applicability in regenerative medicine and biotechnology. The immunomodulatory properties of MSCs make them a promising replacement therapy in various fields of animal research including in canine atopic dermatitis (AD), a skin disease with 10–15% prevalence. Purpose: we investigated the immunomodulatory effects of MSCs in an experimental canine AD model induced by Dermatophagoides farinae extract ointment. Methods: Canine adipose tissue-derived MSCs (cAT-MSCs) were differentiated into mesodermal cell lineages at the third passage. Alterations in immunomodulatory factors in control, AD, and MSC-treated AD groups were evaluated using flow cytometric analysis, enzyme-linked immunosorbent assay, and quantitative reverse transcription polymerase chain reaction. Results: In the MSC-treated AD group, the number of eosinophils decreased and the number of regulatory T cells (Tregs) increased compared to those in the AD group. In addition, the levels of immunoglobulin E (IgE) and prostaglandin E2 were reduced in the MSC-treated AD group compared to those in the AD group. Furthermore, the gene expression levels of filaggrin, vascular endothelial growth factor, and interleukin-5 were higher in the MSC-treated AD group than in the AD group. Conclusion: cAT-MSCs exerted immunomodulatory effects in an AD canine model via a rebalancing of type-1 and -2 T helper cells that correlated with increased levels of Tregs, IgE, and various cytokines.